Analisis Peran Guru Dalam Pencehan dan Penanganan Perilaku Bullying di Kelas 3 SDN Mugarsari - Nina Nurlela; Dudung Suryana; Fajar Nugraha (Pendekar : Jurnal Pendidikan Berkarakter, 2024)
This research was motivated by the existence of several students who experienced bullying behavior while at school and wanted to know the role played by teachers in preventing and handling bullying behavior that occurred towards their students. This research aims to describe: (1) The forms of bullying that occur in grade 3 students at SDN Mugarsari (2) The causes of bullying cases that occur at grade 3 students at SDN Mugarsari (3) The role of teachers in preventing and handling bullying behavior that occurs in participants 3rd grade students at SDN Mugarsari and this research method uses descriptive qualitative research using data collection techniques through observation, interviews and documentation, with the research results obtained namely 1. The forms of bullying behavior that occur are physical bullying, verbal bullying and relational bullying 2. The causal factors are family, school and peer factors. 3. The role of the teacher in preventing and handling bullying behavior is by providing an example of moral conditioning and the role of the teacher as a guide by providing motivation to students and providing advice with the teacher acting as the person who provides it. advice and being able to solve bullying problems among students and teachers also have strategies for handling bullying behavior, namely preventive, repressive and curative strategies.